Aboriginal and Torres Strait Islander health: accuracy of patient self‐report of screening for diabetes, high cholesterol and cervical cancer - Jessica Stewart; Rob Sanson‐Fisher; Sandra Eades (Elsevier, 2016)
Abstract Objective: To determine the accuracy and clinical utility of patient self‐reported screening history. Methods: Aboriginal and Torres Strait Islander patients (≥18 years; n=587) were interviewed on their screening history according to recommended time intervals; these were matched to pathology data. Results: The proportion of patients meeting screening guidelines were 32%(95%CI 26%-39%) for diabetes, 43%(95%CI 38%-47%) for cholesterol and 4.1%(95%CI 2.2%-7.3%) for cervical cancer. When patients reported having had the test, their accuracy (PPV) was low: 38%(95%CI 30%-46%) for diabetes, 47%(95%CI 42%-52%) for cholesterol, 6.5%(95%CI 3.0%-12%) for cervical cancer. However, for the minority of patients who had been screened, positive recall (sensitivity) was high: 94%(95%CI 85%-98%) for diabetes, 83%(95%CI 77%-88%) for cholesterol, 90%(95%CI 55%-98%) for cervical cancer. The accuracy of patient recall was good for those who reported not having been screened (NPV): 90%(95%CI 77%-97%) for diabetes, 70%(95%CI 61%-78%) for cholesterol, 99%(95%CI 95%-100%) for cervical cancer. Conclusions: The results indicate that reliance on self‐report for patients' screening history is inappropriate due to missed opportunities for health gain. However, patients who report not being tested are sufficiently accurate to ensure that ordering the test in this group will involve only a small percentage of unnecessary assays. Implications: GPs often rely on self‐report as a fast and inexpensive way to determine whether a patient requires screening. New strategies are needed to identify patients at risk.